Virus Irradiation and COVID-19 Disease - Durante, Marco; Schulze, Kai; Incerti, Sebastien; Francis, Ziad; Zein, Sara; Guzmán, Carlos Alberto (Frontiers in Physics, 2020)
Virus irradiation has been performed for many decades for basic research studies, sterilization, and vaccine development. The COVID-19 outbreak is currently causing an enormous effort worldwide for finding a vaccine against coronavirus. High doses of -rays can be used for the development of vaccines that exploit inactivated virus. This technique has been gradually replaced by more practical methods, in particular the use of chemicals, but irradiation remains a simple and effective method used in some cases. The technique employed for inactivating a virus has an impact on its ability to induce an adaptive immune response able to confer effective protection. We propose here that accelerated heavy ions can be used to inactivate SARS-CoV-2 viruses with small damage to the spike proteins of the envelope, and can then provide an intact virion for vaccine development.